South Asia open archives (SAOA) (Center for Research Libraries, 2019)
"South Asia Open Archives is a free open-access resource for research and teaching - a rich and growing curated collection of key historical and contemporary sources in arts, humanities and social sciences, from and about South Asia, in English and other languages of the region. SAOA's collection currently contains hundreds of thousands of pages of books, journals, newspapers, census data, magazines, and documents, with particular focus on social & economic history, literature, women & gender, caste & social structure, history of science, and art history & music. SAOA is the product of a collaborative initiative of a broad consortium of 26 current member research libraries in South Asia and around the world. It is enriched by substantial contributions of content, human and material resources from a community of libraries, research centers, archives and other institutions partnering to bring these resources out for global scholarship and pedagogy. Administratively hosted by the Center for Research Libraries, and working in collaboration with the South Asia Materials Project, SAOA is presented online for open access with the advanced database functionalities and user-friendly features that result from our partnership with JSTOR" -- SAOA home page, viewed November 9, 2020.